Representations of local water management : study of the discourse and representations surrounding the implementation of the South African institutional water reform in small irrigation schemes - (:unkn) unknown (My University, 2011)
This research examines the role of small irrigation schemes (SIS) in the South African water management system. We chose to study and interpret the difficulties surrounding the creation of water user associations (WUA), undertaken following the 1998 water reform, in SIS, using a representational approach. This research consists both of a deconstruction of the South African water management policy and an exploration of farmers’ social representations using three case studies. Analysing the interpretations and choices made by officials in the definition and implementation of WUA, the study shows repeated revisions of the institution’s design leading to a gradual exclusion of SIS from participation and undermining of their capacities to contribute meaningfully to the national water management system. The study of farmers’ social representations is conducted using an innovative research design combining discursive and visual methods. It shows depersonalized representations of water management isolated from the concept of control. This concept, central to the political discourse, is at the very core of the difficulties surrounding SIS participation in the national water management system: it symbolizes the discrepancies between farmers’ and officials’ representations and the marginalisation of SIS. Our research concludes by proposing a redefinition of the role of existing irrigation committees in SIS neglected by the water reform until now. It proposes to transform irrigation committees into sub-committees of the WUA, to make them both independent and integrated, to allow them to drive SIS participation, and to establish them as intermediaries between farmers and the national water management policy.
Keywords: African Research